Determinants of Health Professionals' Migration in Africa - Simplice A. Asongu (African Governance and Development Institute (AGDI), 2012)
How do economic prosperity, health expenditure, savings, price-stability, demographic change, democracy, corruption-control, press-freedom, government effectiveness, human development, foreign-aid, physical security, trade openness and financial liberalization play-out in the fight against health-worker crisis when existing emigration levels matter? Despite the acute concern of health-worker crisis in Africa owing to emigration, lack of relevant data has made the subject matter empirically void over the last decades. This paper assesses the theoretical postulations of the WHO report on determinants of health-worker migration. Findings provide a broad range of tools for the fight against health-worker brain-drain. As a policy implication, blanket emigration-control policies are unlikely to succeed equally across countries with different levels of emigration. Thus to be effective, immigration policies should be contingent on the prevailing levels of the crisis and tailored differently across countries with the best and worst records on fighting health worker emigration.
Keywords: D60; F22; I10; J24; O15; 330; Welfare; Health; Human Capital; Migration